FEATURES OF THE QUALITY OF LIFE IN PATIENTS WITH PNEUMONIA - Yarmatov Suvon Tatlibayevich; Normatov Murodjon Buribayevich (Scholar Express Journals, 2023)
Over the past decade, there has been an increased interest in the study of quality of life (QOL) as a new integral indicator describing the most important human functions and allowing for a deep multidimensional analysis of changes in these functions during the development of the disease and their recovery against the background of treatment. Approaches to the study of quality of life in various diseases have the necessary time intervals: short-term and long-term indicators of quality of life. The analysis of the nearest parameters is mainly based on subjective feelings of the patient. In this category, the symptoms of the disease, complaints, temporary disability are considered, which determine a short-term decrease in the quality of life. The assessment of long-term indicators depends on the survival rate of patients and the frequency of necessary hospitalizations. At the same time, symptoms and complaints affecting the longterm prognosis of the disease are analyzed (the rate of progression of the process, persistent disability, reduced life expectancy, loss of social activity, dependence on medications or constant medical supervision monitoring, etc.)
Keywords: Quality of life; functional abilities; general health